Profesi Guru di Era Society 5.0 Pasca Pandemi Covid-19: Profesi Guru dalam Pengembangan Teknologi di Era Society 5.0 Pasca Pandemi Covid-19 - Achmad Muzammil Alfan Nasrullah; Muhammad Imam Sufiyanto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2023)
Amid the improvement of the teacher education system, it will be required with several significant challenges during the era of society 5.0 and after the Covid-19 pandemic, which is still not improving, causing teachers to have to adapt to social technology by applying the Blended Learning system. The teaching profession requires skills that are also based on the concepts and theories of science, also requiring expertise in the field they are engaged. This study aims to discover the challenges of teacher professional ethics that enter technological developments in the era of Society 5.0 after the Covid-19 pandemic. The research method is descriptive qualitative by analyzing directly from the source with a purposive sampling technique which is continued by data collection, observation, interviews, and documentation. The sample used is teachers who actively teach at two levels of education, namely at the MI level and MTS, located in the Sumber Batu area, Pamekasan Regency. The results showed that the teaching profession in society 5.0 after the Covid-19 pandemic revealed that (1) the teaching profession began to adapt to the development of social media, which continues to increase and varies, (2) the teaching profession after the Covid-19 pandemic must also adapt to the existence of a Blended Learning system that has a combination of face-to-face meetings with online systems. Keywords : system, technology, education, profession